2020
DOI: 10.1128/mra.01443-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Dengue Virus Type 2 Epidemic Strains from Reunion Island and the Seychelles

Abstract: Dengue virus has recently reemerged in the southern Indian Ocean islands, causing outbreaks in Reunion Island and the Seychelles. In the present study, we determined the complete genome sequences of closely related clinical isolates of dengue virus type 2 circulating in the Seychelles in 2016 and Reunion Island in 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Of note, in 2015 to 2016, 3 different serotypes (DENV-1, DENV-2, and DENV-3) were identified in 3 travelers returning from Indonesia and Malaysia [ 44 ], highlighting the diversity of DENV variants regularly introduced to the island. Also, comparison of the complete DENV-2 genomes from Reunion (2018) and Seychelles (2016) revealed 99.8% identity [ 48 ], suggesting that these DENV strains may have circulated between the SWIO islands.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, in 2015 to 2016, 3 different serotypes (DENV-1, DENV-2, and DENV-3) were identified in 3 travelers returning from Indonesia and Malaysia [ 44 ], highlighting the diversity of DENV variants regularly introduced to the island. Also, comparison of the complete DENV-2 genomes from Reunion (2018) and Seychelles (2016) revealed 99.8% identity [ 48 ], suggesting that these DENV strains may have circulated between the SWIO islands.…”
Section: Resultsmentioning
confidence: 99%
“…DENV-2 strain RUNJul (also named RUN-18) was isolated from an autochthonous patient diagnosed with mild dengue disease in La Reunion in 2018 [ 1 ]. The sequencing of RUN-18 revealed a close phylogenetic relationship with isolates of the DENV-2 cosmopolitan genotype, which were identified in Seychelles in 2016 [ 1 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very little is still known about the biological characteristics of the DENV-2 strains circulating in SWIO. The phylogenetic analysis showed that the DENV-2 isolates from La Reunion patients diagnosed for dengue disease in 2018 (Reunion/2018 strains), including the prototypical RUJul strain used in this study (GenBank accession number MN272404), belong to the cosmopolitan 1 lineage and, more precisely, to the C1-B sub-lineage [ 1 , 11 ]. The Reunion/2018 DENV-2 sequences also clustered with those identified in 2016 in Seychelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue, like all flaviviruses, is a single-stranded positive sense RNA virus with a genome of about 11 kb, with a 5’-type I cap but without a polyadenylated tail (Colavita et al, 2020; Dang et al, 2020; Kamau et al, 2019; Pascalis et al, 2020; Selisko et al, 2014). The viral genome encodes a long polyprotein which is subsequently processed by both host and viral proteases to generate 10 mature viral proteins.…”
Section: Introductionmentioning
confidence: 99%